The Influence Of Advertising And Brand Image On Purchasing Decisions (Survey On Marjan Syrup Consumers In Tasikmalaya City) - Nursafitri, Lulu; Fitriadi, Budhi Wahyu; Risana, Dudu (Universitas Dehasen Bengkulu, 2025)
This study aims to determine the effect of Advertising and Brand Image simultaneously on Purchasing Decisions for Marjan syrup consumers in Tasikmalaya City. The effect of Advertising and Brand Image partially on Purchasing Decisions for Marjan syrup consumers in Tasikmalaya City. The method used in this research is quantitative method. With a research sample of 100 people as respondents. Sample withdrawal using non-probability precisely using purposive sampling. And the analysis method used is multiple linear regression analysis. Based on the results of the study, it shows that the classification of advertising is very good, Brand Image is included in the classification of very good and Purchasing Decisions are included in the classification of very good. The test results show that simultaneously advertising and Brand Image have a significant effect on purchasing decisions. Partially, advertising has no significant effect on purchasing decisions and Brand Image has a significant effect on purchasing decisions.